2001
DOI: 10.1046/j.1038-5282.2001.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Experience Program at a Metropolitan Paediatric Hospital: Assisting Rural and Metropolitan Allied Health Professionals Exchange Clinical Skills

Abstract: The needs of rural allied health professionals (AHPs) have been widely documented. In particular, problems of professional isolation, lack of professional development opportunities and limited support systems have been highlighted as problems associated with working in rural and remote areas. This research aimed to provide rural and remote AHPs with an opportunity to gain experience in paediatric clinical areas of their choice, to provide rural/remote and metropolitan AHPs with an opportunity to share clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Literature exists describing barriers to CPD for physiotherapists (Titchen 1987;Spalding et al 1999;Pringle and Moore 2001;O'Sullivan 2003) however little refers to CPD and physiotherapists in the context of lone practice (Bithell and Minns Lowe 2000;Solomon et al 2001) and none relates to physiotherapists working in amputee rehabilitation. There are examples of how CPD is or could be achieved for health professionals, however in these studies the context is primarily in relation to geographical isolation (Dunning et al 1994;Bithell and Minns Lowe 2000;Parkin et al 2001).…”
Section: Physiotherapists Amputee Rehabilitation and Lone Workingmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature exists describing barriers to CPD for physiotherapists (Titchen 1987;Spalding et al 1999;Pringle and Moore 2001;O'Sullivan 2003) however little refers to CPD and physiotherapists in the context of lone practice (Bithell and Minns Lowe 2000;Solomon et al 2001) and none relates to physiotherapists working in amputee rehabilitation. There are examples of how CPD is or could be achieved for health professionals, however in these studies the context is primarily in relation to geographical isolation (Dunning et al 1994;Bithell and Minns Lowe 2000;Parkin et al 2001).…”
Section: Physiotherapists Amputee Rehabilitation and Lone Workingmentioning
confidence: 99%
“…The CSP has indicated that more consultant roles are needed in most parts of the UK (Limb 2005). Another approach could be the development of a 'roving' educator (Dunning et al 1994) or a preceptor (Dusmohamed and Guscott 1998;Parkin et al 2001). A preceptor is a skilled practitioner who facilitates professional development and whose roles include that of a needs assessor, educator, mentor, role model, resource person and facilitator of change.…”
Section: Ways Forwardmentioning
confidence: 99%
“…The absence of positive extrinsic incentives is eroding job satisfaction that could improve retention. As demonstrated in the literature (Battye & McTaggart, 2003;Parkin et al, 2001), remote and rural healthcare organisations that encourage and foster the fulfilment of the intrinsic motivation of a professional, as well as providing the extrinsic elements to motivation, have the most potential to recruit and then enhance the longevity of the AH professional in that position.…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of metropolitan peers not respecting skills obtained in remote or rural practice were reported (Parkin et al, 2001) but often found to be untrue when returning to urban positions (Millsteed, 2001). Anxiety concerning the maintenance of professional skills is associated with frustration that specialisation and a career pathway for rural generalist clinical AH professionals does not exist (Beggs & Noh, 1991;Blood et al, 2002;Kaegi et al, 2002;Williams et al, 2007).…”
Section: Frequency Of Mention Of Incentive As Having Amentioning
confidence: 99%
See 1 more Smart Citation